Combining biotechnology with circular bioeconomy: from poultry, swine, cattle, brewery, dairy and urban wastewaters to biohydrogen - Ferreira, Alice (2018)
ABSTRACT: The ability of microalgae to grow in nutrient-rich environments and to accumulate nutrients from wastewaters (WW) makes them attractive for the sustainable and low-cost treatment of WW. The valuable biomass produced can be further used for the generation of bioenergy, animal feed, fertilizers, and biopolymers, among others. In this study, Scenedesmus obliquus was able to remove nutrients from different wastewaters (poultry, swine and cattle breeding, brewery and dairy industries, and urban) with removal ranges of 95-100% for nitrogen, 63-99% for phosphorus and 48-70% for chemical oxygen demand. The biomass productivity using wastewaters was higher (except for poultry) than in synthetic medium (Bristol), the highest value being obtained in brewery wastewater (1025 mg/(L.day) of freeze-dried biomass). The produced biomass contained 31-53% of proteins, 12-36% of sugars and 8-23% of lipids, regardless of the type of wastewater. The potential of the produced Scenedesmus obliquus biomass for the generation of BioH(2) through batch dark fermentation processes with Enterobacter aerogenes was evaluated. The obtained yields ranged, in mL H-2/g Volatile Solids (VS), from 50.1 for biomass from anaerobically digested cattle WW to 390 for swine WW, whereas the yield with biomass cultivated in Bristol medium was 57.6 mL H-2/gvs.